The role of red and white light in optimizing growth and accumulation of plant specialized metabolites at two light intensities in medical cannabis (Cannabis sativa L.) - Holweg, Mexximiliaan M. S. F.; Kaiser, Elias; Kappers, Iris F.; Heuvelink, Ep; Marcelis, Leo F. M. (Frontiers in Plant Science, 2024)
The cultivation of medical cannabis is expanding in controlled environments, driven by evolving governmental regulations for healthcare supply. Increasing inflorescence weight and plant specialized metabolite (PSM) concentrations is critical, alongside maintaining product consistency. Medical cannabis is grown under different spectra and photosynthetic photon flux densities (PPFD), the interaction between spectrum and PPFD on inflorescence weight and PSM attracts attention by both industrialists and scientists. Plants were grown in climate-controlled rooms without solar light, where four spectra were applied: two low-white spectra (7B-20G-73R/Narrow and 6B-19G-75R/2Peaks), and two high-white (15B-42G-43R/Narrow and 17B-40G-43R/Broad) spectra. The low-white spectra differed in red wavelength peaks (100% 660 nm, versus 50:50% of 640:660 nm), the high-white spectra differed in spectrum broadness. All four spectra were applied at 600 and 1200 μmol m -2 s -1 . Irrespective of PPFD, white light with a dual red peak of 640 and 660 nm (6B-19G-75R/2Peaks) increased inflorescence weight, compared to white light with a single red peak of 660 nm (7B-20G-73R/Narrow) (tested at P = 0.1); this was associated with higher total plant dry matter production and a more open plant architecture, which likely enhanced light capture. At high PPFD, increasing white fraction and spectrum broadness (17B-40G-43R/Broad) produced similar inflorescence weights compared to white light with a dual red peak of 640 and 660 nm (6B-19G-75R/2Peaks). This was caused by an increase of both plant dry matter production and dry matter partitioning to the inflorescences. No spectrum or PPFD effects on cannabinoid concentrations were observed, although at high PPFD white light with a dual red peak of 640 and 660 nm (6B-19G-75R/2Peaks) increased terpenoid concentrations compared to the other spectra. At low PPFD, the combination of white light with 640 and 660 nm increased photosynthetic efficiency compared with white light with a single red peak of 660nm, indicating potential benefits in light use efficiency and promoting plant dry matter production. These results indicate that the interaction between spectrum and PPFD influences plant dry matter production. Dividing the light energy in the red waveband over both 640 and 660 nm equally shows potential in enhancing photosynthesis and plant dry matter production.